Migration of Ukraine's personnel potential as a threat to economic security (Economics and region, 2024)
The problem of deepening migration processes and a decline in the economically active population in Ukraine has become more acute in the context of the war. This requires in-depth research and the development of strategic approaches to preserving human resources as the basis of Ukraine's economic security. Based on the official data of the UNFPA and the NBU, the article assesses the existing human resources potential of Ukraine. According to official UNFPA data, the total population of Ukraine in 2024 is 37.9 million people. Of these, according to surveys conducted by the NBU and covered in analytical reports, 60% are economically active, which constitutes the human resources potential of Ukraine. Thus, there is a decline in the human resources potential of Ukraine. The main determinant of external migration of Ukrainians since the beginning of 2022 has been the full-scale invasion of Russia and the introduction of martial law, which significantly changed the socio-economic and demographic situation in the country. The hostilities have led to an increase in the level of danger for the civilian population, destruction of infrastructure, loss of housing and livelihoods, which has significantly intensified migration processes. This is especially true for the regions that were directly affected by the hostilities or are in the high-risk area. The migration of highly qualified specialists in medicine, education, information technology and other strategically important sectors is an obstacle to the realization of economic potential due to the deepening economic imbalances between Ukraine and its partners, and to the successful post-war recovery of the national economy. To mitigate the consequences of mass migration, a comprehensive strategy needs to be developed. This strategy should include measures to improve infrastructure, ensure a stable energy supply, create conditions for the development of entrepreneurship and investment, and expand support programs for the population. It is particularly important to encourage the return of citizens who have temporarily left the country by introducing reintegration programs and involving the Ukrainian diaspora in the country's recovery process.
Keywords: human resources; migration processes; economically active population; economic security